Unearthing the factors governing site specific rates of electronic excitations in multicomponent plasmonic systems and catalysts. (25th February 2019) - Chavez, Steven; Rao, Vishal Govind; Linic, Suljo
Abstract : Direct electronic transitions act as a preferential dissipation pathway for plasmon energy in multicomponent plasmonic systems. Abstract : We use experimental and computational studies of core–shell metal–semiconductor and metal–molecule systems to investigate the mechanism of energy flow and energetic charge carrier generation in multicomponent plasmonic systems. We demonstrate that the rates of plasmon decay through the formation of energetic charge carriers are governed by two factors: (1) the intensity of the local plasmon induced electric fields at a specific location in the multicomponent nanostructure, and (2) the availability of direct, momentum conserved electronic excitations in the material located in that specific location. We propose a unifying physical framework that describes the flow of energy in all multicomponent plasmonic systems and leads us towards molecular control of the energy flow and excited charge carrier generation in these systems.